2013
DOI: 10.4028/www.scientific.net/amr.726-731.2040
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Fe<sub>2</sub>O<sub>3</sub> and its Effect on Co Oxidation in the Chemical Looping Combustion: An Theoretical Account

Abstract: The study focuses on Fe2O3 oxygen carrier for CO oxidation in chemical-looping combustion (CLC) system. Density functional theory (DFT) calculations were performed to detect the performance of Fe2O3 during CLC of CO. Reaction mechanism between CO and Fe2O3 was explored in details, which demonstrates that Fe2O3 with more low-fold O atoms on the surface could promote the activity of the Fe-based oxygen carrier in CLC system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Oxide-based supports, on which the active metal is evenly dispersed to obtain a uniform nanoparticle size, can serve as active sites because interactions between metal nanoparticles and the oxide support can promote catalytic activity . The most commonly used active materials are noble metals such as Pt, ,,,, Pd, Au, and Ag, non-noble metals such as Cu, , Mn, Fe, Co, and Ni, and Hopcalite (CuMnO x ). ,, Recently, owing to the rarity and feasibility of using noble metals, various studies have investigated the use of non-noble metals in CO oxidation; however, compared to their noble metal counterparts, non-noble metal catalysts pose limitations in an actual living space because they often require a high reaction temperature and are affected by moisture inhibition. , In contrast, noble metal catalysts can function in CO oxidation reactions at room temperature and exhibit strong moisture resistance; therefore, they have garnered greater interest for numerous studies. , The process of catalyst manufacturing may have a significant influence on the physicochemical properties and catalytic activity, and many researchers have observed that Pt/TiO 2 catalysts produced using the wet impregnation method acquire excellent CO oxidation ability at room temperature after H 2 reduction above specific temperatures. ,, Seo et al showed that the valence state of Pt in the Pt/TiO 2 catalyst after H 2 reduction was metallic (Pt 0 ) and reported that Pt 0 species affected the reaction activity . Kim et al examined the catalyst properties after Pt/TiO 2 reduction at various temperatures and analyzed the particle size and turnover frequency (TOF) of the active metal.…”
Section: Introductionmentioning
confidence: 99%
“…Oxide-based supports, on which the active metal is evenly dispersed to obtain a uniform nanoparticle size, can serve as active sites because interactions between metal nanoparticles and the oxide support can promote catalytic activity . The most commonly used active materials are noble metals such as Pt, ,,,, Pd, Au, and Ag, non-noble metals such as Cu, , Mn, Fe, Co, and Ni, and Hopcalite (CuMnO x ). ,, Recently, owing to the rarity and feasibility of using noble metals, various studies have investigated the use of non-noble metals in CO oxidation; however, compared to their noble metal counterparts, non-noble metal catalysts pose limitations in an actual living space because they often require a high reaction temperature and are affected by moisture inhibition. , In contrast, noble metal catalysts can function in CO oxidation reactions at room temperature and exhibit strong moisture resistance; therefore, they have garnered greater interest for numerous studies. , The process of catalyst manufacturing may have a significant influence on the physicochemical properties and catalytic activity, and many researchers have observed that Pt/TiO 2 catalysts produced using the wet impregnation method acquire excellent CO oxidation ability at room temperature after H 2 reduction above specific temperatures. ,, Seo et al showed that the valence state of Pt in the Pt/TiO 2 catalyst after H 2 reduction was metallic (Pt 0 ) and reported that Pt 0 species affected the reaction activity . Kim et al examined the catalyst properties after Pt/TiO 2 reduction at various temperatures and analyzed the particle size and turnover frequency (TOF) of the active metal.…”
Section: Introductionmentioning
confidence: 99%
“…CH 4 From the analysis of the data collected in Table 1, it can be concluded that most of the works produced to date do not provide sufficient information with which to model a CLC system using an Fe-based material as an oxygen carrier. Theoretical kinetic studies, relevant from a basic-science point of view, have been also conducted to investigate the mechanisms of interaction between reacting gases and Fe-based oxygen carriers [39][40][41][42][43][44][45][46][47][48], suggesting that the Fe 2 O 3 -support interaction influences material reactivity. However, these works do not provide enough practical information for CLC system design and simulation.…”
Section: Introductionmentioning
confidence: 99%
“…In CLC, the OC is one of the key factors in the CLC system. OC reactivities that promotes redox reactions and bulk oxygen mobility are essential consideration, as they will significantly affect the design of the reactor and the operation of the process. It is necessary to consider OC reaction activity such as promotion of redox reaction, generation of oxygen ions, and body oxygen mobility. , As the common OC, metal oxides, mainly including transition metals such as Ni, Cu, Fe, Co, Mn, and so forth, have the advantages of fast reaction speed, high mechanical stability and recyclability, and high temperature resistance. Because NiO has good kinetic properties and favorable catalytic ability to break carbon–hydrogen bonds, the Ni-based OC can almost achieve 100% conversion of hydrocarbon fuels. , NiO exhibits high reactivity and high upper operating temperature limit. NiO is currently one of the most promising OC materials .…”
Section: Introductionmentioning
confidence: 99%